Delegation of Governor Regulation in Ensuring Utility and Justice - Ni Luh Gede Astariyani; I Gusti Ngurah Wairocana (University of Udayana, 2019)
Delegation means delegation of authority to make Law and Regulations. Article 246 paragraph (1) of Act No. 23 of 2014 on Regional Government stipulates that “to implement the Regional Regulation or over the power of Law and Regulations, the Head of Region shall pass the Head of Region Regulation.” The words